Factors affecting the willingness of sellers in Miag-ao, Iloilo Public Market to avail of formal credit - Cava, Joselito Adolacion
The study identified the factors that affect the willingness to avail of formal credit by the 97 randomly selected sellers in Miagao, Iloilo Public Market. Primary data collected include socio-economic characteristics as well as their business and credit profiles. The multivaritae analysis showed three significant variables that affect the acquirement of formal credit among respondents. These were: 1) if the seller is from the fresh and dried fish section; 2) existence of collateral; and 3) daily repayment. Public market sellers in the fresh and dried fish sectionwere not likely to avail of formal credit (at 5% level of significance). Existence of collateral and daily repayment increased the likelihood of acquirement of formal credit (at 1% and 10% level of significance, respectively). The model was significant at 1% level based on the Chi-square value. The model was able predict 92.*% of thje true willingness to avail of formal credit.